Tingkat Pencemaran Berdasarkan Saprobitas Plankton di Perairan Pelabuhan Benoa, Kota Denpasar, Provinsi Bali - Damayanti, Ni Putu Eva; Karang, I Wayan Gede Astawa; Faiqoh, Elok (Journal of Marine and Aquatic Sciences; Vol 4 No 1 (2018)DO - 10.24843/jmas.2018.v4.i01.96-108, 2017)
Plankton is organism that susceptible to environmental changes that used as indicator of environmental pollution by saprobic index because plankton has important role in affecting the water primary productivity. The research about plankton saprobic in Benoa Harbour is never done before. The aim of this research is to explain the structure of community and the level of plankton saprobic at Benoa Harbour. This research using random sampling  method for determine the station. The result explained that there was 17 species of plankton in the waters of Benoa Harbor from two classes such as  Bacillariophyceae, Dinophyceae  on phytoplankton and from five classes such as Magnoliopsida, Malacostraca, Maxillopoda, Globothalamea  and  Hexanauplia on zooplankton .  The total abundance of plankton ranges from 1.117.172 Individual / Liter- 1.626.163 Individual / Liter. The zooplankton diversity index in the waters of Benoa Harbor ranges from 1.06 to 1.58 and phytoplankton ranges from 1.02 to 155. This indicates that the value of diversity in all observation stations is categorized into low biodiversity. Zooplankton evenness index value in the waters of Benoa Harbor ranged from 0.73-0.88 and phytoplankton ranged from 0.71-0.96. This indicates that the index of evenness is relatively high. The dominant value of zooplankton in the waters of Benoa Harbor ranges from 0.24-0.43 and phytoplankton ranged from 0.22-0.41. This indicates that the dominance is relatively low. Saprobik Index (SI) value ranges from 1.0-1.6 and Tropic Saprobic Index (TSI) ranges from 1.76-1.96. This indicates that the waters of Benoa Harbour is categorized mild contaminated conditions until not contaminated.